PERPUSTAKAAN ADALAH SALAH SATU TEMPAT PEMBELAJARAN SEPANJANG HAYAT - Najla Rustam; Arin Khairunnisa (Yayasan Nusantara Hasana Berdikari, 2023)
The learning process through formal channels is often age-limited, while the independent learning process (